Factors associated with colon cancer early, intermediate and late recurrence after surgery for stage I–III: A 5‐year prospective study. (17th September 2020) - Orive, Miren; Anton, Ane; Gonzalez, Nerea; Aguirre, Urko; Anula, Rocío; Lázaro, Santiago; Redondo, Maximino; Bare, Marisa; Briones, Eduardo; Escobar, Antonio; Sarasqueta, Cristina; Ferreiro, Josefa; et al.
Abstract: Objective: To identify factors associated with early, intermediate or late recurrence colon cancer recurrence. Methods: A total of 1, 732 consecutive patients with colon cancer were recruited and followed for a period of 5 years. Recurrence at 1 year (early), from 1 to 2 (early), from 2 to 3 (intermediate) and from 3 to 5 years (late) was the main outcome measures. Results: Predictors of early recurrence (AUC (95% CI):0.74 (0.70–0.78) were as follows: TNM stage II and III, more than one type of invasion, haemoglobin <10 g/dl, residual tumour (R1), ASA IV, log odds of positive lymph nodes ratio ≥−0.53, perforation, neoadjuvant chemotherapy, infectious complications within 1 year and CEA pre‐ and post‐intervention. These factors remained significant for predicting intermediate (AUC [95% CI]: 0.72 [0.67–0.77]) and late (AUC [95% CI]: 0.68 [0.63–0.74]) recurrence, except for ASA class, log lymph node ratio, perforation and neoadjuvant chemotherapy. Additionally, laterality (left) and medical complications up to 2 years were significant. Conclusions: These risk factors show good predictive ability of early, intermediate and late recurrence, confirming factors established by guidelines and adding some others. They could serve to provide more appropriate and accurate treatment and follow‐up tailored to patient characteristics.